Exploring indirect impacts of COVID-19 on local health systems from the perspectives of health workers and higher education stakeholders in the Philippines using a phenomenological approach - Joemer Maravilla; Jayson Catiwa; Rebecca Guariño; John Federick Yap; Celso Pagatpatan, Jr; Diana Dalisay Orolfo; Jeriel de Silos; Ma. Cynthia Leigh; Jerome Babate; Violeta Lopez (Elsevier, 2023)
Summary: Background: Our study aimed to explore the experiences of stakeholders from local government units, health facilities and higher education institutions on the delivery of non-COVID-19 health services after the initial wave of the pandemic. Methods: Twenty-nine public health workers, thirteen university staff, and four hospital administrators in the Philippines participated. Using a descriptive phenomenological approach, we analysed transcripts from six focus group discussions conducted online between March and June 2021. Findings: The COVID-19 pandemic made the routine health programs inaccessible due to hesitancy among patients to visit health facilities, a shift in public health priorities, and lack of students to augment the existing workforce.Public health workers reported stress and mental health exhaustion. Apart from fear of infection during service provision, public health workers and university staff experienced work overload, pressure to learn new technology, and webinar fatigue. Mental health problems have surfaced as health workers and young people have become more affected while support services remain insufficient.Public health workers have reported actions to maintain service delivery in the new normal such as use of telehealth and social media. However, issues on workforce wellbeing and digital equity posed adaptation challenges. Participants suggested partnership with higher education institutions as pivotal to position local health systems towards recovery. Interpretation: The rapid change in the service landscape highlights the importance of sustainable partnerships, effective workforce management, equitable digital innovations, and promoting mental wellbeing to preserve community, school, and occupational health and rebuild resilient local health systems in low-resourced areas. Funding: This research is proudly supported by the Australia-ASEAN Council, Australian Government Department of Foreign Affairs and Trade.